1992
DOI: 10.1254/jjp.60.377
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Eurystatins A and B, New Prolyl Endopeptidase Inhibitors, on Scopolamine-Induced Amnesia in Rats

Abstract: -Eurystatins A and B, which are produced by Streptomyces eurythermus R353-21, potently inhibited Flavobacterium prolyl endopeptidase (PED) with IC50 values of 0.004 and 0.002,ug/ml, res pectively, while no inhibition was observed against another 5 proteases, even at 100 1tg/ml. The pro tective effect of eurystatins A and B against scopolamine (3 mg/kg, i.p.)-induced amnesia in rats was evaluated by the step-through one-trial passive avoidance method. When administered i.p. 30 min prior to the acquisition trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…POP is implicated in the metabolism of peptide hormones and neuropeptides [2][3][4] although some of the previously identified neuropeptide substrates do not appear to be hydrolyzed in vivo upon closer inspection [5]. Specific inhibitors have been shown to relieve scopolamine-induced amnesia [6], to ameliorate memory loss caused by age, brain lesions, or amnesic drugs [7,8] and were neuroprotective under various conditions [9][10][11], resulting in significant pharmaceutical and academic interest. It was reported that POP has roles in the phosphoinositide cycle [12][13][14], intracellular transport [15], cellular differentiation [16], inflammation [17], angiogenesis [18], and cancer development [19].…”
Section: Introductionmentioning
confidence: 99%
“…POP is implicated in the metabolism of peptide hormones and neuropeptides [2][3][4] although some of the previously identified neuropeptide substrates do not appear to be hydrolyzed in vivo upon closer inspection [5]. Specific inhibitors have been shown to relieve scopolamine-induced amnesia [6], to ameliorate memory loss caused by age, brain lesions, or amnesic drugs [7,8] and were neuroprotective under various conditions [9][10][11], resulting in significant pharmaceutical and academic interest. It was reported that POP has roles in the phosphoinositide cycle [12][13][14], intracellular transport [15], cellular differentiation [16], inflammation [17], angiogenesis [18], and cancer development [19].…”
Section: Introductionmentioning
confidence: 99%
“…All prolyl oligopeptidase inhibitors tested were effective. An amino derivative of SUAM-1221 significantly reversed scopolamine-induced amnesia in mice (Atack et al, 1991), as did eurystatins A and B in the rat (Kamei et al, 1991).…”
mentioning
confidence: 87%
“…Derivatives of SUAM 1221 {N-IIN-(phenyl)butyryl-L-prolyl I pyrrolidine } potently inhibit the rat brain enzyme (K, values = 4-7 nM) (Atack et al, 1991). Two inhibitors isolated from Flavobacterium, termed eurystatins A and B, are potent inhibitors (Kamei et al, 1991), as are peptidyl-a-keto heterocycles (Tsutsumi et al, 1994).…”
mentioning
confidence: 99%
“…Oki and co-workers in 1997 first reported the isolation of Eurystatin A( 28)f rom the cultured broth of Streptomyces eurythermus R353-21 ( Figure 20). [82] It has significant inhibitory activity against serine protease prolyl endopeptidase. [83,86] Synthetic approaches using non-AA routes…”
Section: Isolation Characterization and Biological Activitymentioning
confidence: 99%